The Effect of Human Capital and Entrepreneurship on Lecture Performance (University Entrepreneurship Supporting Lecturer in Indonesia) - Febrisi Dwita; Ela Elliyana; Deni Surapto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
The purpose of this study was to determine the effect of human capital and entrepreneurship on the performance of lecturers (study of entrepreneurship lecturers at universities in Indonesia). The research was conducted at colleges or universities in Indonesia, the research period was October–to December 2021. The research population was lecturers who taught entrepreneurship courses at universities in Indonesia, where the exact number cannot be known. This study used a non-probability purposive sampling technique and for the sample, 156 respondents participated, but only 100 complete questionnaires were deemed usable. The results of the study indicate that human capital has an effect on entrepreneurship for university entrepreneurship lecturers in Indonesia, meaning that competent human capital provides quality and increased entrepreneurship for university lecturers in Indonesia. Human capital owned by entrepreneurship lecturers in Indonesia can create, transfer, and implement knowledge to their students, thereby improving lecturer performance. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh human capital dan entrepreneurship terhadap kinerja dosen (studi dosen kewirausahaan pada perguruan tinggi di Indonesia). Penelitian dilakukan di perguruan tinggi atau universitas di Indonesia, periode penelitian Oktober–Desember 2021. Populasi penelitian adalah dosen yang mengajar mata kuliah kewirausahaan di perguruan tinggi di Indonesia, yang belum dapat diketahui jumlah pastinya. Penelitian ini menggunakan teknik Non-probability Purposive Sampling dan untuk sampel sebanyak 156 responden, namun hanya 100 kuesioner yang lengkap yang dianggap dapat digunakan. Hasil penelitian menunjukkan bahwa human capital berpengaruh terhadap kewirausahaan bagi dosen kewirausahaan perguruan tinggi di Indonesia, artinya modal manusia yang kompeten memberikan kualitas dan peningkatan kewirausahaan bagi dosen perguruan tinggi di Indonesia. Modal manusia yang dimiliki dosen kewirausahaan di Indonesia dapat menciptakan, mentransfer, dan mengimplementasikan ilmu kepada mahasiswanya, sehingga meningkatkan kinerja dosen.